Production and immunological analysis of IgE reactive recombinant egg white allergens expressed in Escherichia coli. Issue 1 (May 2015) - Dhanapala, Pathum; Doran, Tim; Tang, Mimi L.K.; Suphioglu, Cenk
Highlights We successfully produced recombinant versions of Gal d 1, 2 and 3, that were IgE reactive when tested against a pool of egg allergic patients' sera. The IgE reactivity indicates that these recombinant proteins are capable of eliciting an immune response, thus being potential candidates for immunotherapy. We have, for the first time, attempted to produce recombinant versions of all 4 major egg white allergens in E. coli, and successfully produced 3, with only Gal d 4 showing loss of IgE reactivity in the recombinant version. This is the first report of a collective and comparative immunological analysis of all 4 egg white allergens. The significance of this study is the potential use of the IgE reactive recombinant egg white proteins in immunotherapy to treat egg allergic patients.